(untitled) (Research, Society and Development, 2020)
Proved efficiency by Azospirillum brasilense inoculation in maize crop, raises questions about the sequential use of seeds obtained from inoculated plants, that product hormones by bacteria that affect the development of plants in low amount. It aimed to evaluate early development and physiological seed quality reinoculated corn, from cultivation associated with Azospirillum brasilense and nitrogen fertilizer. Experiment was conducted in a randomized block design with factorial 6x2, with six treatments from the previous management of seeds [0, 60 and 120 kg ha-1 N (urea) without inoculation and seed inoculation with A. brasiliense at dose 50, 100 and 150 mL/25 kg of seeds grown with 60 kg ha-1 N], both only with inoculation on previous crop and re-inoculation by maize hybrid seed DKB 285 PRO®. High dose inoculum of A. brasilense (150 ml + 60 kg N ha-1) in the previous crop can be reduced germination and early development, on the other hand, reinoculation reestablish physiological quality and emergence of the seedlings. Inoculation with 100 ml of inoculant + 60 kg ha-1 N followed by reinoculation with A. brasilense stands out in the initial development of maize seedlings for crop rotation. Reinoculated maize seeds with A. brasilense promotes greater root development maize seedlings, increasing surface by roots to water and nutrients absorb from soil, but reduce shoot development.